Analysis of Problems Related to the Elderly Living Alone and Development of an IT Based Support System - Takagi, Miyako; Kato, Yasuhisa; Suzuki, Noriko; Maeno, Joji (Advances in Social Sciences Research Journal, 2023)
A recent trend in Japan is an increase in the number of elderly people aged 65 and over living alone. The problems faced by the elderly living alone include solitary home deaths due to sudden changes in physical condition, as well as the progression of dementia due to lack of human contact. To solve these problems, we have developed an IT-based support system for the elderly living alone. This system may be able to detect sudden changes in the physical condition of elderly people living alone, and through daily conversation with an avatar, alleviate loneliness and delay the progression of dementia.